2016
DOI: 10.1080/23322705.2016.1136540
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of Offending: Human Trafficking in the United States, 2006–2011

Abstract: Research on human trafficking to date reveals certain limitations. First, little empirical research exists that focuses specifically on analyzing occurrences of human-trafficking incidents. Second, investigations of disaggregated data on persons and circumstances remain rare. As a consequence, who does what to whom, and how often, remains unclear. This is problematic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
37
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 68 publications
5
37
0
6
Order By: Relevance
“…Very few human trafficking studies have examined typologies of human traffickers (see Busch-Armendariz, Nsonwu, & Heffron, 2009); most effort has been placed on defining characteristics of victims and understanding pathways into and out of trafficking situations (Denton, 2016; Jones, 2014). Moreover, there is a tendency in the narrative of human trafficking discourse to problematically support the idea of the ideal victim, the “White Slave,” in which women (primarily White women) are not often perpetrators of trafficking, particularly sexual trafficking, and those who do become traffickers are passive actors in a trafficking organization (Denton, 2016; Jones, 2014):Moral and legal distinctions between male and female human traffickers based on perceived notions of female passivity and male aggression should be assumed ineffective and counterproductive to U.S. efforts and obligations to end human trafficking. (Jones, 2014, p. 165)…”
Section: Characteristics Of Human Traffickersmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few human trafficking studies have examined typologies of human traffickers (see Busch-Armendariz, Nsonwu, & Heffron, 2009); most effort has been placed on defining characteristics of victims and understanding pathways into and out of trafficking situations (Denton, 2016; Jones, 2014). Moreover, there is a tendency in the narrative of human trafficking discourse to problematically support the idea of the ideal victim, the “White Slave,” in which women (primarily White women) are not often perpetrators of trafficking, particularly sexual trafficking, and those who do become traffickers are passive actors in a trafficking organization (Denton, 2016; Jones, 2014):Moral and legal distinctions between male and female human traffickers based on perceived notions of female passivity and male aggression should be assumed ineffective and counterproductive to U.S. efforts and obligations to end human trafficking. (Jones, 2014, p. 165)…”
Section: Characteristics Of Human Traffickersmentioning
confidence: 99%
“…However, a social network analysis of U.S. legal cases involving a conviction or plea bargain of traffickers showed that female traffickers ( n = 13, 32.4%) participated in core roles (higher level duties) 55% of the time and male traffickers ( n = 151, 67.6%) 53% of the time, debunking the idea that female traffickers are subservient to male traffickers (Denton, 2016). Moreover, the nationality and ethnicity of the trafficker and their victim were important predictors to victimization.…”
Section: Characteristics Of Human Traffickersmentioning
confidence: 99%
“…Despite growing interest in the topic, the human trafficking literature in general remains notorious for issues such as emotive overclaims, weak research designs, insufficient methodological transparency and questionable assumptions and inferences (e.g. Tyldum and Brunovskis 2005;Denton 2016;Strauss 2016;Zhang 2009;Weitzer 2015). Aside from fundamental definitional and conceptual challenges already discussed (see O'Connell Davidson 2015), accessing relevant participants and data for trafficking research is challenging, especially for quantitative studies.…”
Section: Embedding Indicators In the Labour Trafficking Literaturementioning
confidence: 99%
“…As an often cross‐border crime, human trafficking draws upon structural, global inequalities and market vulnerabilities that create opportunities for exploitation. However, the role of migration has largely been neglected in research on those responsible (Denton ). This leaves a gap in knowledge regarding how to respond to people who are often excluded from systems of justice and returned to the countries, networks, and circumstances, which led to their engagement with the activity with little or no attempt to address other issues in their lives.…”
Section: Existing Research On Convicted Traffickersmentioning
confidence: 99%